Multi-omics analysis of thermal stress response in a zooxanthellate cnidarian reveals the importance of associating with thermotolerant symbionts. Issue 1877 (18th April 2018) - Cziesielski, Maha J.; Liew, Yi Jin; Cui, Guoxin; Schmidt-Roach, Sebastian; Campana, Sara; Marondedze, Claudius; Aranda, Manuel
Abstract : Corals and their endosymbiotic dinoflagellates of the genus Symbiodinium have a fragile relationship that breaks down under heat stress, an event known as bleaching. However, many coral species have adapted to high temperature environments such as the Red Sea (RS). To investigate mechanisms underlying temperature adaptation in zooxanthellate cnidarians we compared transcriptome- and proteome-wide heat stress response (24 h at 32°C) of three strains of the model organism Aiptasia pallida from regions with differing temperature profiles; North Carolina (CC7), Hawaii (H2) and the RS. Correlations between transcript and protein levels were generally low but inter-strain comparisons highlighted a common core cnidarian response to heat stress, including protein folding and oxidative stress pathways. RS anemones showed the strongest increase in antioxidant gene expression and exhibited significantly lower reactive oxygen species (ROS) levels in hospite . However, comparisons of antioxidant gene and protein expression between strains did not show strong differences, indicating similar antioxidant capacity across the strains. Subsequent analysis of ROS production in isolated symbionts confirmed that the observed differences of ROS levels in hospite were symbiont-driven. Our findings indicate that RS anemones do not show increased antioxidant capacity but may have adapted to higher temperatures through association with more thermally tolerant symbionts.